Featured Cover. Issue 1 (21st December 2021) - Falsey, Ann R.; Walsh, Edward E.; Osborne, Richard H.; Vandendijck, Yannick; Ren, Xiaohui; Witek, James; Kang, Diye; Chan, Eric; Scott, Jane; Ispas, Gabriela
Abstract : The cover image is based on the Original Article Comparative assessment of reported symptoms of influenza, respiratory syncytial virus, and human metapneumovirus infection during hospitalization and post‐discharge assessed by Respiratory Intensity and Impact Questionnaire by Ann R. Falsey et al., https://doi.org/10.1111/irv.12903 .